2019
DOI: 10.3390/ijms20030728
|View full text |Cite
|
Sign up to set email alerts
|

Balancing mTOR Signaling and Autophagy in the Treatment of Parkinson’s Disease

Abstract: The mammalian target of rapamycin (mTOR) signaling pathway plays a critical role in regulating cell growth, proliferation, and life span. mTOR signaling is a central regulator of autophagy by modulating multiple aspects of the autophagy process, such as initiation, process, and termination through controlling the activity of the unc51-like kinase 1 (ULK1) complex and vacuolar protein sorting 34 (VPS34) complex, and the intracellular distribution of TFEB/TFE3 and proto-lysosome tubule reformation. Parkinson’s d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(146 citation statements)
references
References 117 publications
1
133
0
Order By: Relevance
“…Neuroinflammation due to an overactivated and/or chronically activated state of microglia is another source of excessive and uncontrolled release of free radicals. Molecular mechanisms underlying these pathophysiological processes are still under evaluation, but recent evidence comes from studies on high-mobility group box 1 (HMGB1) [11], mammalian target of rapamycin (mTOR) signaling [12], and the nuclear factor, erythroid 2 like 2 (Nrf2) [13], among others. Recent breakthroughs from genetic studies revealed that lysosomal system dysfunction is one of the earliest pathogenetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroinflammation due to an overactivated and/or chronically activated state of microglia is another source of excessive and uncontrolled release of free radicals. Molecular mechanisms underlying these pathophysiological processes are still under evaluation, but recent evidence comes from studies on high-mobility group box 1 (HMGB1) [11], mammalian target of rapamycin (mTOR) signaling [12], and the nuclear factor, erythroid 2 like 2 (Nrf2) [13], among others. Recent breakthroughs from genetic studies revealed that lysosomal system dysfunction is one of the earliest pathogenetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In PD brains, MTOR expression and AKT functions are impaired [41]. MTOR over-expression impairs autophagy in genetic PD, enhancing α-synuclein deposition [42], and hsa-miR-128-3p down-regulation could be involved in the up-regulation of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated autophagy has been associated with neurodevelopmental disorders, including autism spectrum disorders 9,[35][36][37] , and neurodegenerative diseases such as PD [38][39][40][41] and amyotrophic lateral sclerosis (ALS) 42,43 , where familial cases are associated with mutations in SOD1 44 . Autophagy is crucial to proper axon guidance, vesicular release, dendritic spine architecture, spine pruning, and synaptic plasticity 3,9,37,45,46 .…”
Section: Ros -Induced Increase In Autophagosomes In Kansl1-deficientmentioning
confidence: 99%